The Role of Digital Marketing Strategies in Enhancing Customer Engagement and Brand Loyalty: A Study of E-Commerce Platforms - Rowi, Armein Sjuhary; Wahyudi, Muhammad Aria; Oswari, Teddy; Purwoko, Bambang (IJBLE Scientific Publications Community Inc., 2024)
This study examines the role of digital marketing strategies in enhancing customer engagement and brand loyalty on e-commerce platforms, emphasizing the mediating effects of trust and perceived value. Using survey data from 400 e-commerce users, the results reveal that personalized, relevant, and frequent marketing efforts significantly enhance customer engagement, which in turn drives brand loyalty. The findings also highlight that trust, characterized by reliability and transparency, and perceived value, defined by quality, convenience, and cost-effectiveness, serve as critical mediators. Structural equation modeling confirms these relationships, providing a comprehensive framework for understanding how digital marketing strategies foster long-term customer loyalty. The study contributes to the theoretical discourse on digital marketing and offers actionable insights for e-commerce businesses aiming to thrive in a competitive marketplace.